Drug Resistance, Clinical Characteristics, and Geographic Distribution of Carbapenem-Resistant Klebsiella pneumoniae Infection in a Northern Province in China - Na Wang; Minghua Zhan; Jianhua Liu; Yao Wang; Yongwang Hou; Caiqing Li; Jia Li; Xuying Han; Jinlu Liu; Yong Chen; et al. (Achievements and Challenges of Medicine and Medical Science Vol. 8, 2024)
Background: Bacterial drug resistance has become a major global challenge in the field of public health and is a serious threat to human health. Since the discovery of carbapenem-resistant K. pneumoniae (CRKP) in the United States in 1996, carbapenem-resistant Enterobacteriaceae (CRE) has spread rapidly worldwide. Purpose: This study analyzed the clinical distribution and drug resistance of carbapenem-resistant Klebsiella pneumoniae (CRKP) strains, the minimum inhibitory concentrations (MIC), MIC50 and MIC90, and the geographical distribution in Hebei Province, China. The study aimed to provide epidemiological research data, formulate appropriate combined treatment schemes, reasonably select antibiotics, and standardize nosocomial infection control schemes. Patients and Methods: A total of 6328 strains of CRKP were collected from 2017 to 2019. The MIC was determined for the drug sensitivity test, and the experimental data were statistically analyzed using WHONET5.6. Susceptibility testing was performed using the minimum inhibitory concentration (MIC) according to the Clinical and Laboratory Standards Institute Results: The detection rate of CRKP increased annually from 13.4% in 2017 to 14.5% in 2018, and 14.6% in 2019. The ratio of males to females was approximately 2:1; 53.6% were elderly, 39% were adults, 4.8% were minors, and 2.5% were newborns. The specimens collected were mainly sputum (70.9%). The resistance rate of CRKP to carbapenems and other \(β\)-lactam antibiotics was found to be increasing, with resistance rates generally greater than 90%. The resistance rate to aminoglycoside antibiotics decreased yearly to approximately 50%, and the resistance rate to quinolones remained unchanged at approximately 80%. From 2017 to 2019, the resistance rate of CRKP in Hebei Province to various antibiotics was high, and the resistance rate to \(β\)-lactam antibiotics increased each year. This study showed that CRKP in Hebei Province mainly caused pneumonia, followed by urinary tract infection, bloodstream infection, wound infection, and abdominal infection. The geographical distribution of CRKP is different in Hebei, and its distribution in other cities in China is uneven. The treatment of CRKP infection remains an intractable problem in clinics. Conclusion: The situation of CRKP resistance is severe in Hebei Province, China. From 2017 to 2019, in Hebei Province, CRKP primarily caused lung infection; males accounted for about two-thirds, and older patients represented the majority of the patient population. The resistance rate to most antibiotics is very high and shows an upward trend. Among them, the resistance rate to polymyxin is low; however, few resistant strains do exist. MIC50 and MIC90 are higher than their MICs. It mainly causes lung infections in elderly men. This study is helpful to improve the diagnosis, treatment, and prevention of CRKP infection in our province.